THE INFLUENCE OF BUSINESS INFORMATION SYSTEMS ON SERBIAN COMPANIES BUSINESS PERFORMANCES - Spasojević, Saša; Vojnović, Boško; Nikolić, Aleksandra (Economics of Agriculture, 2012)
Industrial era has been replaced with the information era of development. Under such influences of surroundings, all the companies have been forced to introduce information systems in their organizations in order to be competitive. Since Serbia technologically tags along the developed part of Europe and bearing in mind that adjusting to changes is the condition of success, this paper aims at answering the question: how many companies in Serbia have an information system, when and how was it introduced and which fields of business were integrated in that way? We came to the conclusion that all the interviewed business subjects use the information system to a greater or lesser extent and mostly for the needs of accounting, sales and supply and that in most cases all fields of business were integrated into a unique IS, which led to the notable savings in business.